Preparation method of composite cast wear-resistant roller
By adding specific elements and alloys to the outer layer, intermediate layer and core of the roll, the problem of low bond strength of the existing composite casting wear-resistant rolls is solved, which significantly improves the toughness and wear resistance of the rolls and extends the service life.
Patent Information
- Application Number
- CN202510405482.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-02
AI Technical Summary
The existing composite cast wear-resistant rolls have low bonding strength with the roller core on the outer layer of the roll, which leads to peeling, cracking and roll breaking accidents, affecting the normal operation of the rolling steel production line.
The rolling roll is prepared by composite casting method, including the outer layer, the intermediate layer and the roller core. By adding calcium silicon alloy and multi-alloy wire to the outer metal melt, copper elements and ferrosilicon particles are added to the intermediate layer, and rare earth magnesium ferrosilicon alloy particles and multi-alloy particles are added to the roller core to ensure the metallurgical bonding effect of each layer.
It significantly improves the toughness, fatigue resistance and wear resistance of the roll, ensures that the roll does not crack or peel during use, extends the service life of the roll, and improves the working efficiency of the roll.
Smart Images

Figure CN119910160A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of roller manufacturing, and in particular to a method for preparing a composite casting wear-resistant roller. Background Art
[0002] Rollers are important consumable parts in steel rolling production. With the development of steel rolling technology and the continuous improvement of the automation level of rolling mills, higher requirements are placed on the toughness and wear resistance of rolls. In order to improve the performance of rolls to meet the needs of rolling mills, roll workers have developed process technologies such as electroslag remelting, spray forming, forging and dual-frequency quenching.
[0003] Chinese invention patent CN103146978A discloses a method for producing high-chromium and low-phosphorus electroslag steel for rolls. The technical solution is: including top and bottom combined blowing converter smelting, LF refining, RH vacuum degassing, billet continuous casting, and bipolar series ingot extraction electroslag remelting process to produce high-chromium and low-phosphorus roll steel. Compared with the traditional electric furnace combined with fixed electroslag remelting process to produce roll steel, the comprehensive yield rate of this invention is increased by 10%. The chromium content in the finished electroslag steel ingot with a diameter of 600mm and a length of 6m is controlled to be above 3.00% and the phosphorus content is below 0.012%. Other chemical elements are also stabilized and optimized, and the surface quality and internal structure are good. This method meets the needs of downstream users very well and achieves good economic benefits. Chinese invention patent CN118080785A also discloses a method for manufacturing a roll neck reinforced roller, which belongs to the field of roll casting, including step 1: casting a cast steel roll according to the chemical composition ratio of the roll neck reinforced roller; step 2: sawing the cast steel roll at the roll neck position to obtain a broken neck roll; step 3: leveling and polishing the sawn surface of the broken neck roll after sawing to ensure that the sawn surface is free of oxidation, impurities, and metallic luster; step 4: preheating the broken neck roll to eliminate stress; step 5: standing the broken neck roll in an electroslag furnace after preheating, with the sawn surface facing up, adding slag, and using electrode ingots of the same material or higher material to electroslag remelt the roll neck to obtain a roll neck reinforced roll; step 6: air cooling the remelted roll neck reinforced roll for 4 to 6 hours to demold; step 7: annealing according to the tempering temperature after demolding, and machining after annealing. The invention can manufacture rolls with high roll neck strength to meet rolling requirements. Chinese invention patent CN112410673A also discloses a method for manufacturing a high-speed steel roll for rolling ultra-high strength steel plates, including smelting and forging roll blanks, preliminary heat treatment and final heat treatment according to chemical composition and weight percentage; the chemical composition and weight percentage are as follows: carbon 0.80~1.20%, silicon 0.20~1.45%, manganese 0.15~0.40%, chromium 7.70~8.30%, molybdenum 1.20~3.00%, vanadium 1.50~2.50%, tungsten 0.80~2.00%, niobium 0.40~0.60%, phosphorus ≤0.020%, sulfur ≤0.015%, the rest is iron and Inevitable impurities; the smelting includes electric furnace smelting, refining outside the furnace, vacuum degassing and spray forming to obtain the steel ingot; the process parameters of the spray forming are as follows: the atomizing gas is nitrogen, the atomizing pressure is 0.3~0.6MPa, the spray distance is 400~500mm, the spray angle is 25~30°, the guide nozzle diameter is 3.5~4.5mm, and the spray temperature is 1450~1550℃; the final heat treatment includes high-temperature overall quenching and high-temperature tempering; the high-temperature overall quenching temperature is 1100~1150℃, and the time is 2~3h; the high-temperature tempering temperature is 520~580℃, and the time is 10~15h.Chinese invention patent CN111270122A also discloses a method for manufacturing a niobium microalloyed cold rolling roll and a niobium microalloyed cold rolling roll. The method for manufacturing a niobium microalloyed cold rolling roll includes s1, smelting: smelting and preparing molten steel containing C, Si, Mn, Cr, Mo, V, Ni, P and S in an electric furnace, and adding niobium iron powder into the molten steel when the molten steel is discharged from the electric furnace to prepare molten steel for cold rolling roll; s2, refining; s3, vacuum treatment; s4, pouring electrode rods and annealing the electrode rods; s5, electroslag remelting ingots; s6, forging: first roughing and then drawing the electrode ingot to prepare the cold rolling roll, and spray cooling the cold rolling roll; s7, heat treating the cold rolling roll; s8, roughing and finishing the cold rolling roll. The manufacturing method of niobium microalloyed cold rolling roll described in the invention can overcome the problem that Nb is easy to burn and difficult to control, so that a cold rolling roll containing niobium elements can be manufactured; and the prepared cold rolling roll has high hardness and wear resistance, and a long service life. Chinese invention patent CN109807554A also discloses a manufacturing process of a cold rolling roll, which includes ingot casting, forging, post-forging heat treatment, rough turning, quenching and tempering, fine turning, surface quenching, cold treatment, low-temperature tempering, fine grinding, surface roughening, and electrochemical passivation steps in sequence; wherein, in the surface quenching step, a dual-frequency quenching machine tool is used to perform dual-frequency quenching treatment on the working surface of the cold rolling roll; in the surface roughening step, an EDT electric spark roughening machine tool is used to roughen the working surface of the cold rolling roll; in the electrochemical passivation step, a pulse electrochemical deburring device is used to deburr and passivate the microscopic peaks on the working surface of the cold rolling roll. This invention improves the service life of EDT texturing cold rolling rolls and the quality of rolled parts, and reduces the frequency of roll replacement. Chinese invention patent CN114032364A also discloses a surface heat treatment process for rolls made of EN~9 material. Before quenching, the rolls are subjected to tempering heat treatment to a hardness of 35~45HSD. The preheating temperature is selected at 350~450℃, and the insulation time is 12~16h. After the preheating and insulation stage, a 50 / 250Hz dual-frequency quenching machine is used for surface heating quenching. During quenching, the heating temperature is selected to be 860~870℃. The 50Hz quenching power is maintained at 510±10KW, and the 250Hz quenching power is maintained at 210±10KW. The descending speed is 100~1000W. The speed is 0.8~1.0mm / s, the rotation speed is 35~40r / min, the quenching water pressure is maintained at 0.8~0.9MPa, and the total quenching time is 50±5min; after quenching, it is cooled in a water pool for 80±10min to complete the quenching process; the hardness of the roller body after quenching is 75~80HSD, and the tempering temperature is 300±10℃ to complete the surface heat treatment process; the hardness of the roller body after heat treatment reaches 45~50HSD, the quality of the roller is good, the hardness uniformity is within 1.5HSD, which is higher than the 3HSD of overall quenching and tempering, and the accident resistance is good.Although the production of rolling mill rolls using processes such as electroslag remelting, spray forming, forging and dual-frequency quenching can improve the performance of rolling mill rolls, it has disadvantages such as low production efficiency, high energy consumption and cost.
[0004] In view of the need for the roller body (roller surface) to have high hardness and excellent wear resistance during use, and the roller neck must have high strength and high toughness to ensure that the roller does not break during use, the composite casting method is used to produce the roller, which is expected to significantly improve the comprehensive performance of the roller. Chinese invention patent CN118531318A discloses a high-boron low-alloy high-speed steel roller and its processing and forming method, the chemical composition of which is (weight percentage): C: 1.2~1.8%, Cr: 4.5~6.5%, W: 1.0~3.0%, Mo: 1.0~3.0%, V: 3.0~5.0%, Al: 0.6~1.2%, Si: 0.8~1.2%, N: 0.05~0.15%, B: 0.04~0.12%, Nb: 0.05~0.20%, Ti: 0.06~0.18%, Y: 0.04~0.15%, Mn<0.5%, P<0.04%, S<0.04%, balance Fe. In the invention, a centrifugal composite casting process is adopted for one-time forming, and the production efficiency is increased by more than 50% compared with the forging process, which effectively improves the production efficiency. At the same time, the centrifugal composite casting process can obtain a uniform organizational structure, reduce defects, improve the quality of the rolling mill, thereby reducing processing steps and reducing production costs. Chinese invention patent CN114737107A also discloses an infinitely cold hardened centrifugal composite casting roller and process for a bright steel finished product frame, wherein the roller comprises an outer layer of the roller and a core of the roller, wherein the chemical composition and mass percentage of the outer layer of the roller are as follows: C 3.00-3.50%, Si 0.60-1.20%, Mn 0.60-1.20%, Cr 1.20-1.80%, Ni 3.50-4.50%, Mo 0.40-0.80%, Nb+V 1.00-2.00%, P≤0.03%, S≤0.025%, Re≥0.02%, and the remainder is Fe and unavoidable impurities; and the chemical composition and mass percentage of the core of the roller are as follows: C 3.00-3.40%, Si 200-2.50%, Mn 0.40-0.60%, Cr 0.10~0.20%, Mg≥0.04%, the balance is Fe and unavoidable impurities; the process includes the following steps: selection of furnace charge; addition of alloy during smelting; casting process; special heat treatment process for rolls; roll performance testing. The invention adds carbide-forming vanadium and strong grain-refining element niobium to improve the physical and chemical properties of the rolls, with high hardness of the working layer, good wear resistance, and less prone to oxidative thermal cracking during rolling.Chinese invention patent CN113369462A also discloses a Cr5 alloy cast steel roller and a production method thereof. The outer layer of the roller body is made of Cr5 alloy steel, and its chemical composition and weight percentage are: C 0.3~0.9%, Si 0.3~0.8%, Mn 0.5~0.8%, P≤0.04%, S≤0.02%, Cr4.5~5.5%, N 0.5~1.0%, Mo 0.3~0.9%, V 0.04~0.2%; the core material is low alloy steel, and its chemical composition and weight percentage are: C 0.5~2.0%, Si 1.1~1.8%, Mn 0.4~1.0%, P≤0.04%, S≤0.02%, Cr≤0.30%, Ni 0~0.5%, Mo 0~0.2%; the roller is obtained by a centrifugal composite casting method. The core of the roll is made of low-alloy steel that matches its outer layer material, which can effectively improve the mechanical properties of the roll core. Without reducing the tensile strength of the roll neck and core, the plasticity and toughness of the roll neck and core are significantly improved, and the accident resistance of the roll is improved. The use of a chilled bottom box can achieve sequential solidification of the roll bottom neck and core molten steel after pouring, reducing the looseness of the bottom neck and core and avoiding serious accidents such as roll breakage. Chinese invention patent CN106636877A also discloses a high chromium cast iron composite cast steel product roll, the chemical composition of the high chromium cast iron composite cast steel product roll is divided into two parts: outer layer and core, wherein the chemical composition of the outer layer is: C 2.80~3.30%; Si 0.50~1.00%; Mn 0.50~1.20%; Cr 10.00~15.00%; Ni 1.50~2.50%; Mo 1.00~1.50%; V 0.20~0.60%; Nb 0.10~0.30%; P≤0.03%; S≤0.025%; the chemical composition of the core is: C 3.00~3.40%; Si 1.80~2.50%; Mn 0.30~0.70%; Nb≥0.10%; Ni≥0.30%; P≤0.03%; S≤0.025%; Mg 0.04~0.07%; the balance is Fe and a small amount of residual elements. Compared with ordinary rollers, this invention improves the surface quality of steel rollers, extends the service life of rollers, reduces the production cost of steel rollers, and enhances the market competitiveness of products through optimized configuration.Chinese invention patent CN106350730A also discloses a high wear-resistant alloy tool steel roll and a manufacturing method thereof, which is used in the front section of the finishing rolling of a tropical continuous rolling mill and a medium-width and thick plate rolling mill. The alloy components and weight percentages of the working layer are C 1.50~2.00%, Si 0.30~1.00%, Mn 0.50~1.20%, P≤0.10%; S≤0.05%, Cr10.0~15.0%, Ni 0.50~2.00%, Mo 0.20~1.50%, V 0.20~2.00%, and the rest are Fe and unavoidable impurities. The invention adopts the process method of centrifugal composite casting and is produced through a quenching heat treatment process of 1020~1100℃×40~80min spray cooling and a three-stage tempering process of 450~550℃×10~20h. It is a rolling mill with high wear resistance, low oxide film growth rate and excellent thermal crack resistance. Chinese invention patent CN105618715A also discloses a wear-resistant high-speed steel composite roller and a preparation method thereof. The composite roller is made of a roller body high-speed steel and a roller core ductile iron through centrifugal composite casting. The chemical composition and mass fraction of the roller body molten steel are controlled at 1.5~2.4% C, 3.5~6.0% Cr, 3.5~6.0% Mo, 3.5~6.0% V, 1.5~3.5% W, 0.6~1.2% Nb, 0.5~1.2% Ni, 0.3~0.8% Si, 0.3~0.8% Mn, S≤0.04%, P≤0.04%, and the balance is Fe. The roller body molten steel is deoxidized and subjected to an out-of-furnace modification treatment with multi-element microalloy steel, and then cast into a roller on a centrifuge. The roller core is made of ductile iron, and the roller is tempered after quenching. It has the characteristics of high hardness, good toughness and wear resistance, and has excellent use effect. However, the composite roll produced by the ordinary centrifugal composite casting method has low bonding strength between the outer layer of the roll and the roll core, and the alloy elements of the outer layer of the roll are easy to penetrate into the roll core, resulting in increased hardness of the roll core and reduced toughness and plasticity. The composite roll produced by the ordinary centrifugal composite casting method is prone to peeling, cracking and roll breakage during use, seriously affecting the normal operation of the steel rolling production line. Summary of the invention
[0005] In view of the above-mentioned problems existing in the existing composite casting wear-resistant rolling roller, the present invention provides a method for preparing a composite casting wear-resistant rolling roller.
[0006] To solve the above technical problems, the technical solution provided by the embodiment of the present invention is: A method for preparing a composite cast wear-resistant roller, wherein the composite cast wear-resistant roller comprises a roller outer layer, an intermediate layer and a roller core, and the preparation method specifically comprises the following steps: S1, heating and melting the raw materials of the outer layer of the roller to obtain an outer layer of molten metal; raising the temperature of the outer layer of molten metal to 1595°C~1630°C, adding silicon-calcium alloy, adjusting the composition to meet the requirements and then tapping the iron into a ladle, then feeding the multi-element alloy wire into the ladle, slagging, pouring, and adding low-melting-point protective slag after the pouring is completed; wherein the raw materials of the multi-element alloy wire include ferroboron powder, silicon-calcium-barium alloy powder, aluminum-magnesium alloy particles and nano-TiC powder; S2, after heating and melting the raw materials of the middle layer of the roller and the metal copper, sequentially adding ferrosilicon alloy, ferromanganese alloy and metal tin to obtain a middle layer molten metal; heating the middle layer molten metal to 1495°C-1530°C, tapping part of the middle layer molten metal into the first iron ladle, adding ferrosilicon particles along with the tapping process, pouring part of the middle layer molten metal when the inner surface temperature of the outer layer of the roller is 1290°C-1360°C, and adding protective slag after the pouring is completed; S3, placing rare earth magnesium ferrosilicon alloy particles and silicon calcium barium alloy powder at the bottom of the second molten iron ladle, and then tapping the remaining middle layer of molten metal into the second molten iron ladle, skimming off the slag, and obtaining the roller core ductile iron molten iron; when the inner surface temperature of the roller middle layer is 1242°C~1295°C, pouring the roller core ductile iron molten iron, adding multi-element alloy particles along with the pouring process, after the pouring is completed, taking out and slowly cooling, rough processing, and heat treatment to obtain a composite cast wear-resistant roller; wherein the multi-element alloy particles include metal antimony, metal bismuth and rare earth ferrosilicon alloy.
[0007] Compared with the prior art, the composite casting wear-resistant roller preparation method provided by the present invention adds silicon-calcium alloy to the outer metal melt to fully deoxidize the metal melt. The addition of calcium element helps the inclusions to change from rod-shaped and block-shaped to spherical, promotes the discharge of inclusions from the metal melt, improves the purity of the outer metal melt, and improves the fatigue resistance of the roller. At the same time, boron iron powder, silicon-calcium-barium alloy powder, aluminum-magnesium alloy particles and nano-TiC powder are fed into the outer metal melt of the ladle in the form of multi-element alloy wire, wherein aluminum and magnesium elements have excellent deoxidation and desulfurization effects, and magnesium elements have excellent effects of refining the outer layer of the roller (i.e., the working layer of the roller), which can significantly improve the toughness and fatigue resistance of the roller, ensure that the roller does not crack and peel off during use, and the added boron is solid-dissolved in the roller matrix, which can significantly improve the hardenability of the roller. The addition of nano-TiC can not only refine the solidification structure of the roller, but also significantly improve the wear resistance of the roller. In addition, the composite effect of nano-TiC and calcium and barium can promote the network-distributed carbides in the working layer of the roller to become isolated carbides, thereby significantly improving the impact toughness of the roller, ensuring that the roller does not crack or peel off during use, and significantly extending the service life of the roller.
[0008] The addition of copper to the middle layer can not only refine the solidification structure of cast iron, but also increase the amount of pearlite in cast iron, thereby improving the strength and toughness of cast iron; tin can gather at the graphite-austenite interface, hinder the diffusion of carbon into graphite, promote the solid solution of carbon in austenite, and contribute to the formation of pearlite, thereby improving the strength of cast iron. At the same time, the addition of ferrosilicon particles during the tapping process of the middle layer molten metal can increase the number of graphite solidification cores, refine the graphite structure, prevent the appearance of white cast structure in the middle layer, and significantly reduce the brittleness of the middle layer.
[0009] The roll size is large, the roll core molten iron is poured in a static state, and the solidification time is long. Ordinary ductile iron is prone to spheroidization recession, which significantly reduces the strength and toughness of ductile iron. In the process of pouring the roll core molten iron, the present invention adds multi-element alloy particles mixed with antimony, bismuth and rare earth ferrosilicon into the flow, which can significantly increase the number of graphite cores, prevent graphite recession, ensure that the roll core has a good spheroidization effect, and thus ensure that the composite roll core has excellent strength and toughness.
[0010] As a specific embodiment of the present invention, in S1, the raw materials of the outer layer of the roller include scrap steel, a carburizer and an iron alloy. The scrap steel includes Q235 scrap steel, scrap high-speed steel, scrap high-chromium cast iron or scrap high-nickel chromium-molybdenum cast iron. The addition amount of the carburizer and the iron alloy can be obtained by conventional adjustment according to the requirements of the outer layer composition of the roller, and the present invention does not make any special restrictions.
[0011] As a specific implementation of the present invention, if in S1, the scrap steel selects scrap high-speed steel and Q235 scrap steel, the composition mass fraction of the outer layer molten metal is: C 1.50%~2.20%, Si 0.30%~1.20%, Mn 0.40%~1.20%, P ≤0.030%, S≤0.025%, Cr 3.00%~8.00%, Ni 0.00%~1.50%, Mo 2.00%~8.00%, V2.00%~9.00%, W 0.30%~2.00%, Nb 0.30%~2.00%, and the remainder is Fe and unavoidable impurities.
[0012] Using scrap high-speed steel and Q235 as raw materials and controlling the composition of the outer metal melt within the above range can make the roller have the advantages of high hardness, red hardness and good wear resistance.
[0013] As a specific implementation of the present invention, if in S1, the scrap steel selects Q235 scrap steel and waste high-chromium cast iron, the composition mass fraction of the outer layer metal melt is: C 2.30%~3.30%, Si 0.30%~1.00%, Mn 0.50%~1.20%, P≤0.10%, S≤0.05%, Cr 18.01%~22.00%, Ni 0.50%~1.70%, Mo 1.01%~3.00%, V0.20%~0.60%, and the remainder is Fe and unavoidable impurities.
[0014] Using waste high-chromium cast iron and Q235 as raw materials and controlling the composition of the molten metal in the outer layer of the roll within the above range, the roll can contain more M7C3 carbides, thereby improving the wear resistance of the roll.
[0015] As another specific embodiment of the present invention, if in S1, the scrap steel selects Q235 scrap steel and waste high-nickel chromium-molybdenum cast iron, the composition mass fraction of the outer layer metal melt is: C 2.90%~3.60%, Si 0.60%~2.00%, Mn0.40%~1.20%, P≤0.10%, S≤0.05%, Cr 1.00%~3.00%, Ni 3.01%~5.00%, Mo 0.20%~2.00%, V0.50%~2.50%, W 0.00%~8.00%, Nb 0.00%~1.00%, and the remainder is Fe and unavoidable impurities.
[0016] Using waste high-nickel-chromium-molybdenum cast iron and Q235 as raw materials and controlling the composition of the molten metal in the outer layer of the roll within the above range, the roll can have excellent hardenability and wear resistance, and the martensitic matrix can be obtained in the cast state without the need for subsequent high-temperature quenching treatment.
[0017] As a specific implementation of the present invention, two medium frequency induction furnaces are used to smelt the outer layer molten metal of the roll, the middle layer of the roll and the roll core molten metal respectively. Using one electric furnace to smelt the middle layer and the roll core molten iron at the same time can not only reduce equipment investment and simplify smelting operations, but also effectively reduce production energy consumption and improve production efficiency.
[0018] Furthermore, in S1, the amount of the silicon-calcium alloy added is 0.20% to 0.25% of the mass of the molten metal.
[0019] Furthermore, in S1, the chemical composition and mass fraction of the silicon-calcium alloy are: Ca 31.27%~33.50%, Si 58.06%~62.75%, C≤1.0%, Al≤2.4%, and the remainder is Fe and unavoidable impurities.
[0020] Furthermore, in S1, the feeding amount of the multi-element alloy wire is 7.5m / t~8.0m / t of molten metal, and the feeding speed is 10m / min~12m / min.
[0021] Furthermore, in S1, the mass fraction of each raw material in the multi-element alloy wire is: 15% to 16% of ferroboron powder, 46% to 48% of silicon-calcium-barium alloy powder, 32% to 34% of aluminum-magnesium alloy particles, and 4.0% to 4.5% of nano-TiC powder, and the sum of each component is 100%.
[0022] The boron element in the ferroboron powder forms hard phases such as ferroboride with iron, which improves the surface hardness and wear resistance of the roll, refines the grains, and improves the overall mechanical properties. Silicon calcium barium alloy powder removes oxygen from the molten metal by deoxidation, reduces the surface tension to improve the casting performance, and its alloying effect can also improve the performance of the roll. Aluminum-magnesium alloy particles can not only further deoxidize and refine, but also improve the strength and toughness of the roll through solid solution strengthening, while improving the surface quality. Nano-TiC powder improves the surface hardness and high-temperature dimensional stability of the roll by virtue of its high hardness, high wear resistance and good high-temperature stability. Its good interface bonding with the metal matrix can effectively transfer loads and prevent crack propagation. These components work together to comprehensively improve the performance and service life of the roll.
[0023] Furthermore, in S1, the particle size of the ferroboron powder is 15-25 mesh, the particle size of the silicon-calcium-barium alloy powder is 20-30 mesh, and the particle size of the aluminum-magnesium alloy particles is 0.5 mm-3.5 mm.
[0024] Furthermore, in S1, the method for preparing the multi-element alloy wire comprises the following steps: Boron iron powder, silicon calcium barium alloy powder, aluminum magnesium alloy particles and nano-TiC powder are uniformly mixed to obtain mixed powder; the mixed powder is coated with a low-carbon steel belt and rolled to obtain a multi-element alloy wire with a diameter of 13mm-14mm.
[0025] In combination with the above, as a specific implementation, the chemical composition of the low carbon steel strip is: C 0.08%~0.19%, Si 0.40%~0.49%, Mn 3.67%~3.95%, Al 2.08%~2.55%, S≤0.030%, P≤0.035%, the balance is Fe and inevitable impurities. The thickness of the low carbon steel strip is 0.55mm~0.65mm. The chemical composition of the low carbon steel strip is: C0.08%~0.19%, Si 0.40%~0.49%, Mn 3.67%~3.95%, Al 2.08%~2.55%, S≤0.030%, P≤0.035%, the balance is Fe and inevitable impurities; the thickness of the low carbon steel strip is 0.55mm~0.65mm.
[0026] It should be noted that in S1, the slag is removed 8 to 10 minutes after the multi-element alloy wire is fed.
[0027] Further, in S1, the chemical composition of the ferroboron powder is: B 19.09%~20.84%, C≤0.5%, Si≤2%, Al≤0.5%, S≤0.01%, P≤0.1%, and the balance is Fe and unavoidable impurities; The chemical composition of the silicon-calcium-barium alloy powder is: Si 42.16%-44.38%, Ca 10.26%-11.85%, Ba 10.40%-11.86%, C≤0.8%, P≤0.04%, S≤0.06%, and the balance is Fe and unavoidable impurities; The chemical composition of the aluminum-magnesium alloy powder is: Al 72%-75%, Mg 25%-28%.
[0028] Furthermore, in S1, the casting mold rotation speed is 900r / min~1100r / min, and the casting temperature is 1430℃~1460℃.
[0029] Furthermore, in S1, the low melting point protective slag is an anti-oxidation O The amount of glass slag added is 0.8kg / m 2 ~1.0kg / m 2 .
[0030] It should be noted that low-melting-point protective slag needs to be added immediately after the outer layer is cast to prevent oxidation of the outer metal, improve the metallurgical bonding effect of the outer metal and the middle metal, and ensure that the roller will not crack or fall off during use.
[0031] As a specific embodiment of the present invention, the raw materials of the middle layer include scrap steel and a recarburizer. The scrap steel is Q235 scrap steel. The amount of each raw material added can be conventionally adjusted according to the composition requirements of the molten metal in the middle layer, and the present invention does not make any special restrictions. The recarburizers of the outer layer and the middle layer can be selected from conventional recarburizers in the art, such as petroleum coke powder, and the present invention does not make any special restrictions.
[0032] As a specific implementation of the present invention, the metal copper is a copper plate.
[0033] Furthermore, in S2, the composition of the intermediate layer metal melt is: C 3.22%~3.45%, Si 1.35%~1.58%, Mn 0.59~0.76%, Cu 0.52%~0.65%, Sn 0.05%~0.08%, P≤0.080%, S≤0.040%, and the remainder is Fe and unavoidable impurities.
[0034] Furthermore, in S2, the chemical composition of the ferrosilicon particles is: Si 74.80%~76.17%, Al≤1.0%, Ca≤1.0%, Mn≤0.4%, Cr≤0.3%, P≤0.035%, S≤0.020%, C≤0.10%, and the balance is Fe and unavoidable impurities.
[0035] Furthermore, in S2, the particle size of the ferrosilicon particles is 5 mm to 12 mm.
[0036] Furthermore, in S2, the amount of the ferrosilicon particles added is 0.7% to 0.9% of the mass of the molten metal in the intermediate layer.
[0037] Furthermore, in S2, the pouring temperature of the partial intermediate layer molten metal is 1355° C. to 1385° C., and the pouring thickness of the intermediate layer is 16 mm to 22 mm.
[0038] Controlling the pouring temperature of the middle layer molten metal at 1355℃~1385℃ and pouring the middle layer molten metal when the inner surface temperature of the outer layer of the roller is 1290℃~1360℃ can prevent the outer layer of the roller and the middle layer molten metal from mixing together, so that the middle layer can play a good insulating role, avoiding the alloy elements in the outer layer of the roller from entering the roller core layer, and ensuring that the roller core layer has a good spheroidizing effect and excellent strength and toughness.
[0039] The invention overcomes the problem that the outer metal of the common bimetallic centrifugal composite roller is easily mixed into the ductile iron of the roller core, resulting in poor spheroidization effect of the roller core and insufficient toughness of the ductile iron of the roller core.
[0040] Furthermore, in S2, the protective slag is anhydrous sodium tetraborate, and the amount of the protective slag added is 0.40 kg / m 2 ~0.45kg / m 2 .
[0041] Furthermore, in S3, the particle size of the rare earth magnesium ferrosilicon alloy particles is 7 mm to 12 mm; and the particle size of the silicon calcium barium alloy powder is 20 mesh to 30 mesh.
[0042] Furthermore, in S3, the amount of the rare earth magnesium ferrosilicon alloy particles added is 1.2% to 1.4% of the mass of the remaining intermediate layer metal melt, and the amount of the silicon calcium barium alloy powder added is 0.5% to 0.6% of the mass of the remaining intermediate layer metal melt.
[0043] Furthermore, in S3, the chemical composition of the rare earth magnesium ferrosilicon alloy particles is: Mg 11.15%~11.82%, RE 2.21%~2.68%, Si 40.16%~41.96%, Ca 2.08%~2.66%, and the remainder is Fe and unavoidable impurities.
[0044] Furthermore, in S3, the chemical composition of the rare earth ferrosilicon alloy is: RE 27.42%~29.27%, Si 38.66%~41.51%, Mn<3.0%, Ca<5.0%, Ti<3.0%, and the balance is Fe and unavoidable impurities.
[0045] Furthermore, in S3, the pouring temperature of the roller core molten metal is 1325°C to 1350°C.
[0046] Furthermore, in S3, the mass percentage of each raw material in the multi-element alloy particles is: metal antimony 9%-10%, metal bismuth 3%-4%, rare earth ferrosilicon 86%-88%, and the sum of each component is 100%.
[0047] Furthermore, in S3, the particle size of the multi-element alloy particles is 0.8 mm to 3.5 mm.
[0048] Furthermore, in S3, the amount of the multi-element alloy particles added is 0.25% to 0.30% of the mass of the molten metal entering the inner roller core of the casting mold.
[0049] It should be noted that in S3, the roll is taken out from the mold 8h~12h after the pouring is completed and placed in a slow cooling pit for slow cooling.
[0050] Further, in S3, the heat treatment includes quenching and tempering treatment, wherein the quenching temperature is 1020°C~1080°C, and the quenching time is 3h~5h; the tempering temperature is 520°C~580°C, and the tempering time is 18h~22h.
[0051] It should be noted that if the outer layer is high-speed steel, the heat treatment method is quenching + tempering. High-nickel-chromium-molybdenum cast iron is directly tempered. High-chromium cast iron can be treated by quenching + tempering or direct tempering.
[0052] Furthermore, in S3, the heat treatment is a tempering treatment, the tempering temperature is 350°C to 400°C, and the treatment time is 22h to 28h.
[0053] It should be noted that, in the present invention, the outer layer and the middle layer of the roller are formed by centrifugal casting, and the roller core is formed by static top casting.
[0054] Compared with the prior art, the present invention has the following advantages: (1) The present invention realizes the smelting of three kinds of molten metals by two electric furnaces, with high production efficiency and low energy consumption.
[0055] (2) Due to the addition of the intermediate layer and the use of flow casting to inoculate the roll core, the composite cast wear-resistant roll of the present invention has a good spheroidization effect on the roll core and the roll neck ductile iron, and the spheroidization rate exceeds 95%. The tensile strength of the roll core and the roll neck ductile iron exceeds 550 MPa, and the elongation exceeds 12%, ensuring that the composite cast wear-resistant roll will not break during use.
[0056] (3) The outer layer and the middle layer of the composite cast wear-resistant roller of the present invention are formed by centrifugal composite casting, and have high bonding strength. The middle layer and the roller core are molten iron smelted in the same furnace. The middle layer and the roller core have good composite effect, and a strong metallurgical bond is achieved, ensuring that the roller will not peel off or de-sleeve accidents during use.
[0057] (4) The outer layer of the composite cast wear-resistant roller of the present invention has fine solidification structure, isolated carbides, good toughness and wear resistance. Under the same working conditions, the wear resistance of the roller of the present invention is improved by more than 30% compared with the ordinary centrifugal composite roller. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 The schematic diagram of the structure of the composite roller prepared in Example 1 of the present invention; wherein 11 is a roller neck; 12 is an outer layer (roller body working layer); 13 is an intermediate layer; 14 is a roller core; Figure 2 This is a schematic diagram of core filling after the composite casting wear-resistant rolling roll used in an embodiment of the present invention is closed; wherein, 1 is a riser box; 2 is an end cover; 3 is a casting mold; 4 is an outer layer of metal; 5 is an intermediate layer of cast iron; 6 is a base box; 7 is a refractory brick; and 8 is a bottom plate. DETAILED DESCRIPTION
[0059] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0060] In order to better illustrate the present invention, further examples are given below.
[0061] The particle size of the ferroboron powder used in the following examples is 15-25 mesh, the particle size of the silicon-calcium alloy powder is 20-30 mesh, the particle size of the aluminum-magnesium alloy particles is 0.5-3.5 mm, the particle size of the ferrosilicon particles is 5-12 mm, and the particle size of the rare earth magnesium-ferrosilicon alloy particles is 7-12 mm.
[0062] In the following examples, the impact toughness is in accordance with GB / T 229-2020 Metallic Materials Charpy Pendulum Impact Test Method; the elongation and tensile strength are in accordance with GB / T228.1-2020 Metallic Materials Tensile Test Part 1: Room Temperature Test Method; and the hardness is in accordance with GB / T 13313-2008 Roller Shore Hardness Test Method.
[0063] Example 1 This embodiment provides a method for preparing a composite cast wear-resistant roller. Figure 1 The composite cast wear-resistant roller is composed of three parts: the roller outer layer 12, the middle layer 13 and the roller core 14. The specific preparation process includes the following steps: S1, two medium frequency induction furnaces are used to smelt the molten metal of the roller outer layer 12, the middle layer 13 and the roller core 14 respectively; the roller outer layer 12 is high speed steel; The smelting process of the outer layer 12 material is as follows: waste high-speed steel, Q235 scrap steel, petroleum coke carburizer, and ferroalloy are mixed, heated and melted to obtain an outer layer of molten metal (chemical composition: C 1.93%, Si 0.77%, Mn 0.64%, P 0.028%, S 0.020%, Cr 5.28%, Ni 0.61%, Mo 3.76%, V 4.09%, W 0.84%, Nb 0.52%, the remainder being Fe and unavoidable impurities); when the temperature of the outer layer of molten metal rises to 1630°C, silicon-calcium alloy is added (the chemical composition and mass fraction of the silicon-calcium alloy are: Ca 31.27%, Si 62.75%, C 0.55%, Al 1.63%, the balance is Fe and unavoidable impurities), the amount of silicon-calcium alloy added accounts for 0.20% of the mass of the inner and outer layers of the furnace molten metal, and the composition is adjusted in front of the furnace and qualified before being taken out of the furnace to the ladle; after the outer layer of the molten metal has all entered the ladle, the multi-element alloy wire is fed into the outer layer of the molten metal in the ladle by a wire feeder, and the amount of multi-element alloy wire added is 8.0m / t of molten metal; the wire feeding speed of the multi-element alloy wire in the ladle is controlled at 10m / min; after the multi-element alloy wire is added to the molten metal for 8 minutes, the molten metal in the ladle is slag-scraped and allowed to stand, and when the temperature drops to 1460℃, it is poured into the casting mold 3 on the horizontal centrifuge, and the rotation speed of the casting mold 3 is 900r / min; after the outer layer 12 molten metal is poured, the anti-oxidation flux is immediately added O The amount of glass slag added is 0.8 kg / m 2 ; The multi-element alloy wire includes: 15% ferroboron powder, 48% silicon-calcium-barium alloy powder, 33% aluminum-magnesium alloy particles and 4% nano-TiC powder. The chemical composition of ferroboron powder is: B 19.09%, C 0.37%, Si 0.84%, Al 0.26%, S 0.008%, P0.056%, the balance is Fe and inevitable impurities; the chemical composition of silicon-calcium-barium alloy powder is: Si 42.16%, Ca 11.85%, Ba 10.40%, C 0.48%, P 0.033%, S 0.047%, the balance is Fe and inevitable impurities; the chemical composition of aluminum-magnesium alloy particles is: Al 72%, Mg 28%; The preparation method of the multi-element alloy wire comprises the following steps: mixing ferroboron powder, silicon-calcium-barium alloy powder, aluminum-magnesium alloy particles and nano-TiC powder uniformly, packaging the uniformly mixed powders with a low-carbon mild steel strip with a thickness of 0.55-0.65 mm, and rolling the mixed powders into a multi-element alloy wire with a diameter of φ13 mm on an alloy cored wire unit; the chemical composition of the low-carbon mild steel strip is: C0.08%, Si 0.49%, Mn 3.67%, Al 2.55%, S 0.021%, P 0.032%, and the balance is Fe and unavoidable impurities; S2, the smelting process of the molten iron of the middle layer 13 and the roller core 14 is: the scrap steel, petroleum coke carburizer and copper plate are mixed and heated and melted in another medium frequency induction furnace, and after the molten iron is melted, ferrosilicon, ferromanganese and metallic tin are added in sequence, and the chemical composition and mass fraction of the molten iron in the furnace are controlled at: C 3.22%, Si 1.58%, Mn 0.59%, Cu 0.65%, Sn 0.08%, S0.037%, P 0.061%, and the balance is Fe and inevitable impurities; when the temperature of the molten iron rises to 1495℃, part of the molten iron of the middle layer 13 is first discharged from the furnace into the molten iron ladle Ⅰ, and when the molten iron is discharged from the furnace, ferrosilicon particles (chemical composition: Si74.80%, Al 0.64%, Ca 0.39%, Mn 0.11%, Cr 0.17%, P 0.032%, S 0.013%, C 0.05%, the balance being Fe and unavoidable impurities), the amount of ferrosilicon particles added is 0.7% of the mass of the molten iron entering the ladle Ⅰ; the molten iron in the ladle Ⅰ is poured into the casting mold 3 on the centrifuge in step S1; before pouring, the inner surface temperature of the outer layer 12 of the roller in the casting mold 3 is measured with a non-contact thermometer, and when the temperature is 1290-1317°C, the middle layer 13 cast iron is poured on the centrifuge, the pouring temperature of the middle layer 13 cast iron is 1355°C, the pouring thickness of the middle layer 13 is 16 mm, and the protective agent anhydrous sodium tetraborate is added immediately after the pouring of the middle layer 13 is completed, and the amount of anhydrous sodium tetraborate added is 0.40kg / m 2 ; S3, all the remaining molten iron in the furnace of step S2 is discharged into the ladle II, rare earth magnesium silicon iron alloy particles (chemical composition: Mg 11.15%, Ce 2.68%, Si 40.16%, Ca 2.66%, the balance is Fe and unavoidable impurities) and silicon calcium barium alloy powder are placed at the bottom of the ladle II in advance, the amount of rare earth magnesium silicon iron alloy and silicon calcium barium alloy powder added accounts for 1.2% and 0.5% of the mass fraction of the molten iron entering the ladle II respectively, and ductile iron molten iron is obtained after spheroidization and inoculation treatment, and then slag is removed and allowed to stand; 2 minutes after the casting of the roller middle layer 13 cast iron is completed, the inner surface temperature of the roller middle layer 13 cast iron is measured with a non-contact thermometer, and when the temperature is 1 When the temperature is 242-1276℃, the roller core 14 is top-casted with ductile iron molten iron in a static state, and the molten iron pouring temperature is 1325℃; during the pouring process of the ductile iron molten iron of the roller core 14, multi-element alloy particles mixed with antimony, bismuth and rare earth ferrosilicon are added along with the molten iron flow, and the amount of multi-element alloy particles added accounts for 0.25% of the mass fraction of the ductile iron molten iron entering the casting mold; 8 hours after the pouring of the ductile iron molten iron of the roller core 14 is completed, the roller is taken out and put into a slow cooling pit, and then rough processing is performed; The multi-component alloy particles are composed of 9% by mass of antimony, 4% by mass of bismuth and 87% by mass of rare earth ferrosilicon; the multi-component alloy particle size is 0.8-3.5 mm; the chemical composition and mass fraction of the rare earth ferrosilicon are: Ce 27.42%, Si 41.51%, Mn 1.07%, Ca, 2.84%, Ti 0.95%, and the balance is Fe and unavoidable impurities; S4, quenching and tempering treatment is performed on the rough-machined roller (high-speed steel roller), the quenching heating temperature is 1050℃, the holding time is 4h, air cooling, the tempering heating temperature is 550℃, the holding time is 20h, furnace cooling, and finally fine machining is performed to the specified size and accuracy to obtain composite cast wear-resistant high-speed steel roller.
[0064] The hardness of the outer layer 12 of the roller is 84.3 HSD, and the room temperature impact toughness of the outer layer 12 is 14.8 J / cm 2 The tensile strength of the roll neck 14 (roll core 14) is 575 MPa, and the elongation exceeds 12.7%.
[0065] After testing, the volume fraction of inclusions in the outer layer is 0.11%, and the volume fraction of inclusions in the roller core is 0.13%.
[0066] Example 2 This embodiment provides a method for preparing a composite cast wear-resistant roller. Figure 1 The composite cast wear-resistant roller is composed of three parts: the roller outer layer 12, the middle layer 13 and the roller core 14. The specific preparation process includes the following steps: S1, two medium frequency induction furnaces are used to smelt the molten metal of the roller outer layer 12 and the molten iron of the middle layer 13 and the roller core 14 respectively; the roller outer layer 12 is high chromium cast iron; The smelting process of the outer layer 12 material is as follows: Q235 scrap steel, waste high chromium cast iron, petroleum coke carburizer, and ferroalloy are mixed and heated to melt to obtain an outer layer of molten metal (chemical composition: C 2.97%, Si 0.85%, Mn 0.82%, P 0.062%, S0.041%, Cr 18.87%, Ni 0.91%, Mo 2.05%, V 0.38%, the remainder being Fe and unavoidable impurities); when the temperature of the outer layer of molten metal rises to 1595°C, silicon-calcium alloy (chemical composition: Ca 33.50%, Si 58.06%, C 0.27%, Al1.03%, the balance is Fe and unavoidable impurities), the amount of silicon-calcium alloy added accounts for 0.25% of the mass fraction of the inner and outer layers of the furnace molten metal, and the composition is adjusted in front of the furnace and then it is taken out of the furnace to the ladle after it is qualified; after the outer layer of the molten metal has all entered the ladle, the multi-element alloy wire is fed into the outer layer of the molten metal in the ladle by a wire feeder, and the amount of multi-element alloy wire added is 7.5m / t of molten metal; the wire feeding speed of the multi-element alloy wire in the ladle is controlled at 12m / min; 10min after the multi-element alloy wire is added to the molten metal, the molten metal in the ladle is slag-scraped and allowed to stand, and when the temperature drops to 1430℃, it is poured into the casting mold 3 on the horizontal centrifuge, and the rotation speed of the casting mold 3 is 1100r / min; after the outer layer 12 molten metal is poured, an anti-oxidation flux is immediately added O The amount of glass slag added is 1.0 kg / m 2 ; The multi-element alloy wire includes: 16% ferroboron powder, 46% silicon-calcium-barium alloy powder, 33.5% aluminum-magnesium alloy particles and 4.5% nano-TiC powder. The chemical composition and mass fraction of the ferroboron are: B 20.84%, C 0.26%, Si 1.05%, Al 0.41%, S 0.009%, P 0.048%, and the balance is Fe and inevitable impurities. The chemical composition and mass fraction of the silicon-calcium-barium alloy are: Si 44.38%, Ca 10.26%, Ba 11.86%, C 0.51%, P 0.030%, S 0.044%, and the balance is Fe and inevitable impurities. The chemical composition and mass fraction of the aluminum-magnesium alloy are: Al 75%, Mg 25%.
[0067] The preparation method of the multi-element alloy wire comprises the following steps: mixing ferroboron powder, silicon-calcium-barium alloy powder, aluminum-magnesium alloy particles and nano-TiC powder uniformly, packaging the uniformly mixed powders with a low-carbon mild steel strip with a thickness of 0.55-0.65 mm, and rolling the mixed powders into a multi-element alloy wire with a diameter of φ14 mm on an alloy cored wire unit; the chemical composition of the low-carbon mild steel strip is: C0.19%, Si 0.40%, Mn 3.95%, Al 2.08%, S 0.029%, P 0.034%, and the balance is Fe and unavoidable impurities; S2, the smelting process of the molten iron of the middle layer 13 and the roller core 14 is as follows: the scrap steel, petroleum coke carburizer and copper plate are mixed and heated to melt in another medium frequency induction furnace. After the molten iron is melted, ferrosilicon, ferromanganese and metallic tin are added in sequence, and the chemical composition and mass fraction of the molten iron in the furnace are controlled at: C 3.45%, Si 1.35%, Mn 0.76%, Cu 0.52%, Sn 0.05%, S0.036%, P 0.069%, and the balance is Fe and inevitable impurities; when the temperature of the molten iron rises to 1530℃, part of the molten iron of the middle layer 13 is first discharged from the furnace into the molten iron ladle Ⅰ, and when the molten iron is discharged from the furnace, ferrosilicon particles (chemical composition: Si76.17%, Al 0.76%, Ca 0.52%, Mn 0.33%, Cr 0.19%, P 0.032%, S 0.010%, C 0.08%, the remainder being Fe and unavoidable impurities), the amount of ferrosilicon particles added accounts for 0.9% of the mass fraction of the molten iron entering the ladle Ⅰ; the molten iron in the ladle Ⅰ is poured into the casting mold 3 on the centrifuge in step S1; before pouring, the inner surface temperature of the outer layer 12 of the roller in the casting mold 3 is measured with a non-contact thermometer, and when the temperature is 1330-1360°C, the middle layer 13 cast iron molten iron is continued to be poured on the centrifuge, the pouring temperature of the middle layer 13 cast iron molten iron is 1385°C, the pouring thickness of the middle layer 13 is 22mm, and the protective agent anhydrous sodium tetraborate is added immediately after the pouring of the middle layer 13 is completed, and the amount of anhydrous sodium tetraborate added is 0.45 kg / m 2 ; S3, all the remaining molten iron in the furnace of step S2 is discharged into the ladle II, and rare earth magnesium ferrosilicon alloy (chemical composition: Mg 11.82%, Ce 2.21%, Si 41.96%, Ca 2.08%, the balance is Fe and unavoidable impurities) and silicon calcium barium alloy powder are placed at the bottom of the ladle II in advance, and the addition amount of rare earth magnesium ferrosilicon alloy and silicon calcium barium alloy powder accounts for 1.4% and 0.6% of the mass fraction of the molten iron entering the ladle II respectively; the molten iron is subjected to spheroidization and inoculation treatment to obtain ductile iron, and then the slag is removed and allowed to stand; 4 minutes after the casting of the middle layer 13 of the roller is completed, the inner surface temperature of the cast iron of the middle layer 13 of the roller is measured with a non-contact thermometer, and when the temperature is 1 When the temperature is 261-1295℃, the roller core 14 is top casted with ductile iron molten iron in a static state, and the molten iron pouring temperature is 1350℃; during the pouring process of the ductile iron molten iron of the roller core 14, multi-element alloy particles mixed with antimony, bismuth and rare earth ferrosilicon are added along with the molten iron flow, and the amount of multi-element alloy particles added accounts for 0.30% of the mass fraction of the ductile iron molten iron entering the casting mold; 10 hours after the pouring of the ductile iron molten iron of the roller core 14 is completed, the roller is taken out and put into a slow cooling pit, and then rough processing is performed; The multi-component alloy particles include: 10% antimony, 4% bismuth and 86% rare earth ferrosilicon; the multi-component alloy particle size is 0.8-3.5 mm. The chemical composition and mass fraction of the rare earth ferrosilicon are: 29.27% Ce, 41.51% Si, 2.07% Mn, 3.80% Ca, 0.95% Ti, and the balance is Fe and unavoidable impurities.
[0068] S4, quenching and tempering the rough-machined roll (high chromium cast iron roll), quenching heating temperature 1025℃, holding time 4h, air cooling, tempering heating temperature 525℃, holding time 22h, furnace cooling, and finally fine machining to the specified size and accuracy to obtain a composite cast wear-resistant high chromium cast iron roll.
[0069] The hardness of the outer layer 12 of the roller is 81.7 HSD, and the room temperature impact toughness of the outer layer 12 is 10.8 J / cm 2 The tensile strength of the roll neck 14 (roll core 14) is 565 MPa, and the elongation exceeds 13.2%.
[0070] After testing, the volume fraction of inclusions in the outer layer of the composite roller was 0.08%, and the volume fraction of inclusions in the roller core was 0.11%.
[0071] Example 3 This embodiment provides a method for preparing a composite cast wear-resistant roller. Figure 1 The composite cast wear-resistant roller is composed of three parts: the roller outer layer 12, the middle layer 13 and the roller core 14. The specific preparation process includes the following steps: S1, two medium frequency induction furnaces are used to smelt the molten metal of the roller outer layer 12, the middle layer 13 and the roller core 14 respectively; the roller outer layer 12 is high nickel-chromium-molybdenum cast iron; The smelting process of the outer layer 12 material is as follows: Q235 scrap steel, waste high nickel chromium molybdenum cast iron, petroleum coke carburizer, and ferroalloy are mixed and heated to melt to obtain an outer layer metal melt (chemical composition: C 3.27%, Si 1.17%, Mn 0.88%, P 0.073%, S0.040%, Cr 2.15%, Ni 3.84%, Mo 0.95%, V 0.87%, Nb 0.28%, the balance is Fe and unavoidable impurities); when the temperature of the outer layer metal melt rises to 1613°C, silicon calcium alloy (chemical composition: Ca32.35%, Si 60.80%, C0.46%, Al 2.13%, the balance is Fe and unavoidable impurities), the amount of silicon-calcium alloy added accounts for 0.22% of the mass of the inner and outer layers of the furnace molten metal, and the composition is adjusted in front of the furnace and then it is taken out of the furnace to the ladle after it is qualified; after the outer layer of the molten metal has all entered the ladle, the multi-element alloy wire is fed into the outer layer of the molten metal in the ladle by a wire feeder, the amount of the multi-element alloy wire added is 7.8m / t of the molten metal, and the wire feeding speed of the multi-element alloy wire in the ladle is controlled at 11m / min; 9 minutes after the multi-element alloy wire is added to the molten metal, the molten metal in the ladle is slag-scraped and allowed to stand, and when the temperature drops to 1446℃, it is poured into the casting mold 3 on the horizontal centrifuge, and the rotation speed of the casting mold 3 is 1000r / min; after the outer layer 12 molten metal is poured, the anti-oxidation flux is immediately added O The amount of glass slag added is 0.9 kg / m 2 ; The multi-element alloy wire includes: 15.5% ferroboron powder, 47% silicon-calcium-barium alloy powder, 33.3% aluminum-magnesium alloy particles and 4.2% nano-TiC powder. The chemical composition and mass fraction of the ferroboron are: B 19.94%, C 0.28%, Si 1.26%, Al 0.19%, S0.005%, P 0.041%, and the balance is Fe and inevitable impurities. The chemical composition and mass fraction of the silicon-calcium-barium alloy are: Si 42.82%, Ca 10.95%, Ba 10.81%, C 0.48%, P 0.039%, S 0.028%, and the balance is Fe and inevitable impurities. The chemical composition and mass fraction of the aluminum-magnesium alloy are: Al 74%, Mg 26%.
[0072] The preparation method of the multi-element alloy wire comprises the following steps: mixing ferroboron powder, silicon-calcium-barium alloy powder, aluminum-magnesium alloy particles and nano-TiC powder uniformly, packaging the uniformly mixed powders with a low-carbon mild steel strip with a thickness of 0.55-0.65 mm, and rolling the mixed powders into a multi-element alloy wire with a diameter of φ13.5 mm on an alloy cored wire unit; the chemical composition and mass fraction of the low-carbon mild steel are: C 0.13%, Si 0.46%, Mn 3.80%, Al 2.26%, S 0.027%, P 0.034%, and the balance is Fe and unavoidable impurities; S2, the smelting process of the molten iron of the middle layer 13 and the roller core 14 is: the scrap steel, petroleum coke carburizer and copper plate are mixed and heated to melt in another medium frequency induction furnace, and after the molten iron is melted, ferrosilicon, ferromanganese and metallic tin are added in sequence, and the chemical composition and mass fraction of the molten iron in the furnace are controlled at: C 3.36%, Si 1.42%, Mn 0.69%, Cu 0.58%, Sn 0.06%, S0.031%, P 0.047%, and the balance is Fe and inevitable impurities; when the temperature of the molten iron rises to 1516℃, part of the molten iron of the middle layer 13 is first discharged from the furnace into the molten iron ladle Ⅰ, and when the molten iron is discharged from the furnace, ferrosilicon particles (chemical composition: Si75.38%, Al 0.66%, Ca 0.47%, Mn 0.15%, Cr 0.21%, P 0.031%, S 0.014%, C 0.08%, the remainder being Fe and unavoidable impurities), the amount of ferrosilicon particles added is 0.8% of the mass of the molten iron entering the ladle Ⅰ; the molten iron in the ladle Ⅰ is poured into the casting mold 3 on the centrifuge in step S1; before pouring, the inner surface temperature of the outer layer 12 of the roller in the casting mold 3 is measured with a non-contact thermometer, and when the temperature is 1310-1348°C, the middle layer 13 cast iron molten iron is poured on the centrifuge, the pouring temperature of the middle layer 13 cast iron molten iron is 1372°C, the pouring thickness of the middle layer 13 is 20 mm, and the protective agent anhydrous sodium tetraborate is added immediately after the pouring of the middle layer 13 is completed, and the amount of anhydrous sodium tetraborate added is 0.42 kg / m 2 ; S3, all the remaining molten iron in the furnace of step S2 is discharged into the ladle II, and rare earth magnesium silicon iron alloy particles (chemical composition: Mg 11.73%, Ce 2.54%, Si 40.92%, Ca 2.57%, the balance is Fe and unavoidable impurities) and silicon calcium barium alloy powder are placed at the bottom of the ladle II in advance, and the addition amount of rare earth magnesium silicon iron alloy particles and silicon calcium barium alloy powder accounts for 1.3% and 0.55% of the mass fraction of the molten iron entering the ladle II respectively; the molten iron is spheroidized and inoculated to obtain ductile iron molten iron, and then the slag is removed and allowed to stand; 3 minutes after the casting of the roller middle layer 13 cast iron is completed, the inner surface temperature of the roller middle layer 13 cast iron is measured with a non-contact thermometer, and when When the temperature is 1257-1288°C, the roll core 14 is top-casted with ductile iron molten iron in a static state, and the molten iron pouring temperature is 1343°C; during the pouring process of the ductile iron molten iron of the roll core 14, multi-element alloy particles mixed with antimony, bismuth and rare earth ferrosilicon are added along with the molten iron flow, and the amount of multi-element alloy particles added accounts for 0.28% of the mass of the ductile iron molten iron entering the casting mold; 9 hours after the pouring of the ductile iron molten iron of the roll core 14 is completed, the roll is taken out and put into a slow cooling pit, and then rough processing is performed; The multi-component alloy particles include: 9% antimony, 3% bismuth and 88% rare earth ferrosilicon; the multi-component alloy particle size is 0.8-3.5 mm; the chemical composition and mass fraction of the rare earth ferrosilicon are: Ce 28.63%, Si 39.75%, Mn 2.05%, Ca 4.27%, Ti1.84%, and the balance is Fe and unavoidable impurities; S4, tempering the rough-machined roll (high nickel-chromium-molybdenum cast iron roll), with a tempering heating temperature of 385°C, a holding time of 25h, furnace cooling, and finally fine machining to the specified size and accuracy to obtain a composite cast wear-resistant high nickel-chromium-molybdenum cast iron roll.
[0073] The hardness of the outer layer 12 of the roller is 83.6 HSD, and the room temperature impact toughness of the outer layer 12 is 7.3 J / cm 2 The tensile strength of the roll neck 14 (roll core 14) is 580 MPa, and the elongation exceeds 12.5%.
[0074] After testing, the volume fraction of inclusions in the outer layer of the composite roller was 0.09%, and the volume fraction of inclusions in the roller core was 0.13%.
[0075] The roll core and roll neck prepared in Example 1 to Example 3 have good spheroidization effect. After testing, the spheroidization rate exceeds 95%.
[0076] Used in hot strip rolling mills, under the same working conditions, the millimeter steel excess of the composite wear-resistant roller (high-speed steel roller) prepared in Example 1 of the present invention reaches 22,000 tons, while the millimeter steel excess of the ordinary centrifugal composite casting high-speed steel roller is only 16,500 tons, and the wear resistance is improved by more than 30% compared with the ordinary centrifugal composite casting high-speed steel roller.
[0077] Used in hot strip rolling mills, under the same working conditions, the millimeter steel excess of the composite wear-resistant roller (high chromium cast iron roller) prepared in Example 2 of the present invention reaches 10,000 tons, while the millimeter steel excess of the ordinary centrifugal composite casting high-speed steel roller is only 7,200 tons. The wear resistance is improved by more than 38% compared with the ordinary centrifugal composite casting high chromium cast iron roller.
[0078] For hot rolling bar mills, under the same working conditions, the millimeter steel passing rate of the composite wear-resistant roll (high nickel-chromium-molybdenum cast iron roll) prepared in Example 3 of the present invention reaches 3400 tons, and the millimeter steel passing rate of the ordinary centrifugal composite casting high nickel-chromium-molybdenum cast iron roll reaches 2510 tons, and the wear resistance is improved by more than 35% compared with the ordinary centrifugal composite casting high nickel-chromium-molybdenum cast iron roll.
[0079] The present invention realizes the smelting of three kinds of molten metals by two electric furnaces, with high production efficiency and low energy consumption. By controlling the smelting and casting process of the outer layer, the middle layer and the roller core, the roller core and the roller neck have good spheroidization effect, the spheroidization rate exceeds 95%, the tensile strength of the roller core and the roller neck exceeds 550MPa, the elongation exceeds 12%, the hardness of the roller outer layer exceeds 80HSD, and the room temperature impact toughness exceeds 7J / cm 2 The bonding strength of each layer is high. The middle layer and the roller core are cast from molten iron smelted in the same furnace. The composite effect is good, which achieves a strong metallurgical bond and ensures that the rollers will not peel off or de-sleeve during use. It significantly extends the service life of the rollers, improves the operating efficiency of the rolling mill, and has good economic and social benefits.
[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite cast wear-resistant roller, characterized in that: The composite cast wear-resistant roller comprises a roller outer layer, an intermediate layer and a roller core, and the preparation method thereof specifically comprises the following steps: S1, heating and melting the raw materials of the outer layer of the roller to obtain an outer layer of molten metal; raising the temperature of the outer layer of molten metal to 1595°C~1630°C, adding silicon-calcium alloy, adjusting the composition to meet the requirements and then taking it out of the furnace and placing it in a casting ladle, then feeding multi-element alloy wire into the casting ladle, slagging, pouring, and adding low-melting-point protective slag after the pouring is completed; wherein the raw materials of the multi-element alloy wire include ferroboron powder, silicon-calcium-barium alloy powder, aluminum-magnesium alloy particles and nano-TiC powder; S2, after heating and melting the raw materials of the middle layer of the roller and the metal copper, sequentially adding ferrosilicon alloy, ferromanganese alloy and metal tin to obtain a middle layer molten metal; heating the middle layer molten metal to 1495°C-1530°C, tapping part of the middle layer molten metal into the first iron ladle, adding ferrosilicon particles along with the tapping process, pouring part of the middle layer molten metal when the inner surface temperature of the outer layer of the roller is 1290°C-1360°C, and adding protective slag after the pouring is completed; S3, placing rare earth magnesium ferrosilicon alloy particles and silicon calcium barium alloy powder at the bottom of the second molten iron ladle, and then tapping the remaining middle layer of molten metal into the second molten iron ladle, skimming off the slag, and obtaining the roller core ductile iron molten iron; when the inner surface temperature of the roller middle layer is 1242°C~1295°C, pouring the roller core ductile iron molten iron, adding multi-element alloy particles along with the pouring process, after the pouring is completed, taking out and slowly cooling, rough processing, and heat treatment to obtain a composite cast wear-resistant roller; wherein the multi-element alloy particles include metal antimony, metal bismuth and rare earth ferrosilicon alloy.
2. The method for preparing a composite cast wear-resistant roller according to claim 1, characterized in that: In S1, the composition mass fraction of the outer layer metal melt is: C 1.50%~2.20%, Si 0.30%~1.20%, Mn 0.40%~1.20%, P ≤0.030%, S≤0.025%, Cr 3.00%~8.00%, Ni 0.00%~1.50%, Mo 2.00%~8.00%, V 2.00%~9.00%, W 0.30%~2.00%, Nb 0.30%~2.00%, and the balance is Fe and unavoidable impurities; or In S1, the composition mass fraction of the outer layer metal melt is: C 2.30%~3.30%, Si 0.30%~1.00%, Mn0.50%~1.20%, P≤0.10%, S≤0.05%, Cr 18.01%~22.00%, Ni 0.50%~1.70%, Mo 1.01%~3.00%, V 0.20%~0.60%, and the balance is Fe and unavoidable impurities; or In S1, the composition mass fractions of the outer layer metal melt are: C 2.90%~3.60%, Si 0.60%~2.00%, Mn0.40%~1.20%, P≤0.10%, S≤0.05%, Cr 1.00%~3.00%, Ni 3.01%~5.00%, Mo 0.20%~2.00%, V0.50%~2.50%, W 0.00%~8.00%, Nb 0.00%~1.00%, and the balance is Fe and unavoidable impurities.
3. The method for preparing a composite cast wear-resistant roller according to claim 1, characterized in that: In S1, the amount of the silicon-calcium alloy added is 0.20% to 0.25% of the mass of the molten metal; and / or In S1, the chemical composition and mass fraction of the silicon-calcium alloy are: Ca 31.27%~33.50%, Si 58.06%~62.75%, C≤1.0%, Al≤2.4%, and the balance is Fe and unavoidable impurities; and / or In S1, the feeding amount of the multi-element alloy wire is 7.5m / t~8.0m / t of molten metal, and the feeding speed is 10m / min~12m / min.
4. The method for preparing a composite cast wear-resistant roller according to claim 1, characterized in that: In S1, the mass fraction of each raw material in the multi-element alloy wire is: 15% to 16% of ferroboron powder, 46% to 48% of silicon-calcium-barium alloy powder, 32% to 34% of aluminum-magnesium alloy particles, and 4.0% to 4.5% of nano-TiC powder, and the sum of each component is 100%; and / or In S1, the particle size of the ferroboron powder is 15-25 mesh, the particle size of the silicon-calcium-barium alloy powder is 20-30 mesh, and the particle size of the aluminum-magnesium alloy particles is 0.5 mm-3.5 mm; and / or In S1, the preparation method of the multi-element alloy wire comprises the following steps: mixing ferroboron powder, silicon-calcium-barium alloy powder, aluminum-magnesium alloy particles and nano-TiC powder uniformly to obtain a mixed powder; coating the mixed powder with a low-carbon steel strip, rolling, and obtaining a multi-element alloy wire with a diameter of 13 mm to 14 mm; the chemical composition of the low-carbon steel strip is: C 0.08% to 0.19%, Si 0.40% to 0.49%, Mn 3.67% to 3.95%, Al 2.08% to 2.55%, S≤0.030%, P≤0.035%, and the remainder is Fe and unavoidable impurities; the thickness of the low-carbon steel strip is 0.55 mm to 0.65 mm; and / or In S1, the chemical composition of the ferroboron powder is: B 19.09%~20.84%, C≤0.5%, Si≤2%, Al≤0.5%, S≤0.01%, P≤0.1%, and the balance is Fe and unavoidable impurities; The chemical composition of the silicon-calcium-barium alloy powder is: Si 42.16%-44.38%, Ca 10.26%-11.85%, Ba 10.40%-11.86%, C≤0.8%, P≤0.04%, S≤0.06%, and the balance is Fe and unavoidable impurities; The chemical composition of the aluminum-magnesium alloy powder is: Al 72%-75%, Mg 25%-28%.
5. The method for preparing a composite cast wear-resistant roller according to claim 1, characterized in that: In S1, the casting speed is 900r / min~1100r / min, and the casting temperature is 1430℃~1460℃; and / or In S1, the low melting point protective slag is anti-oxidation O The amount of glass slag added is 0.8kg / m 2 ~1.0kg / m 2 .
6. The method for preparing a composite cast wear-resistant roller according to claim 1, characterized in that: In S2, the composition of the intermediate layer metal melt is: C 3.22%~3.45%, Si 1.35%~1.58%, Mn 0.59%~0.76%, Cu 0.52%~0.65%, Sn0.05%~0.08%, P≤0.080%, S≤0.040%, and the balance is Fe and unavoidable impurities.
7. The method for preparing a composite cast wear-resistant roller according to claim 1, characterized in that: In S2, the chemical composition of the ferrosilicon particles is: Si 74.80% to 76.17%, Al≤1.0%, Ca≤1.0%, Mn≤0.4%, Cr≤0.3%, P≤0.035%, S≤0.020%, C≤0.10%, and the balance is Fe and unavoidable impurities; and / or In S2, the particle size of the ferrosilicon particles is 5 mm to 12 mm; and / or In S2, the amount of ferrosilicon particles added is 0.7% to 0.9% of the mass of the molten metal in the intermediate layer; and / or In S2, the pouring temperature of the molten metal of the intermediate layer is 1355°C to 1385°C, and the pouring thickness of the intermediate layer is 16mm to 22mm; and / or In S2, the protective slag is anhydrous sodium tetraborate, and the amount added is 0.40 kg / m 2 ~0.45kg / m 2 .
8. The method for preparing a composite cast wear-resistant roller according to claim 1, characterized in that: In S3, the particle size of the rare earth magnesium ferrosilicon alloy particles is 7 mm to 12 mm; and / or In S3, the amount of the rare earth magnesium ferrosilicon alloy particles added is 1.2% to 1.4% of the mass of the remaining intermediate layer metal melt, and the amount of the silicon calcium barium alloy powder added is 0.5% to 0.6% of the mass of the remaining intermediate layer metal melt; and / or In S3, the chemical composition of the rare earth magnesium ferrosilicon alloy particles is: Mg 11.15%~11.82%, RE 2.21%~2.68%, Si 40.16%~41.96%, Ca 2.08%~2.66%, and the balance is Fe and unavoidable impurities; In S3, the chemical composition of the rare earth ferrosilicon alloy is: RE 27.42%~29.27%, Si 38.66%~41.51%, Mn<3.0%, Ca<5.0%, Ti<3.0%, and the balance is Fe and unavoidable impurities.
9. The method for preparing a composite cast wear-resistant roller according to claim 1, characterized in that: In S3, the pouring temperature of the ductile iron molten iron of the roller core is 1325° C. to 1350° C.; and / or In S3, the mass fraction of each raw material in the multi-element alloy particles is: metal antimony 9%-10%, metal bismuth 3%-4%, rare earth ferrosilicon 86%-88%, and the sum of each component is 100%; and / or In S3, the particle size of the multi-element alloy particles is 0.8 mm to 3.5 mm; and / or In S3, the amount of the multi-element alloy particles added is 0.25% to 0.30% of the mass of the ductile iron liquid entering the inner roller core of the casting mold.
10. The method for preparing a composite cast wear-resistant roller according to claim 1, characterized in that: In S3, the heat treatment includes quenching and tempering, wherein the quenching temperature is 1020°C to 1080°C, and the quenching time is 3h to 5h; the tempering temperature is 520°C to 580°C, and the tempering time is 18h to 22h; or In S3, the heat treatment is tempering treatment, the tempering temperature is 350°C to 400°C, and the treatment time is 22h to 28h.
Citation Information
Patent Citations
Method for producing high-chromium low-phosphorus electroslag steel for rollers
CN103146978A
Abrasion-resistance high-speed steel composite roller and preparation method thereof
CN105618715A
High-wear-resistance alloy tool steel roll and manufacturing method thereof
CN106350730A
High chromium cast iron composite casting section steel product roller and preparation method thereof
CN106636877A
Manufacturing process for cold-rolling roll
CN109807554A
Cited By
High-strength and high-toughness alloy material as well as preparation method and application thereof
CN120082785A